Learning Effectiveness and Satisfaction in Study Groups: A Consideration of the Moderating Factors - Pang, Elvi; Hung, Humphry (EDUCARE, 2012)
ABSTRACT: The emerging predominance of group learning in the business world represents a significant trend of group work assignments in the context of formal education. Group learning effectiveness and satisfaction has been analyzed on the basis of traditional theories of group dynamics. However, the assessment of learning effectiveness and satisfaction has its uniqueness and requires special attention. Based upon equity theory, we propose a model to highlight the significant impact of workload equity and mutual collaboration on membersâ performance and satisfaction in the group learning process. We conduct a study to validate the relationship and the results support our proposition. In addition, with reference to predicted outcome value theory, we propose that information transparency has a highly significant moderating effect in the group learning process. Hence, the findings of this study are consistent with the results of previous studies on team effectiveness that found conflicts and individual satisfaction to be negatively associated, and interpersonal understanding amongst team members to be positively correlated with team learning. On top of this observation, our study contributes to literature by highlighting the significance of information transparency in the group learning process. Finally, some implications, limitations, and recommendations of our study are discussed.KEY WORDS: Group learning, learning effectiveness and satisfaction, workload equity, mutual collaboration, and interpersonal understanding.Â Â About the Authors: Elvi Pang is a Lecturer at the Department of Management and Marketing HKPU (Hong Kong Polytechnic University) in Hong Kong, China; and Dr. Humphry Hung is Senior Lecturer at the same Department. They can be contacted at: Department of Management and Marketing HKPU in Hong Kong, Cina. Phone: (852)-2766-7357. E-mail: mshung@polyu.edu.hkHow to cite this article? Pang, Elvi & Humphry Hung. (2012). âLearning Effectiveness and Satisfaction in Study Groups: A Consideration of the Moderating Factorsâ in EDUCARE: International Journal for Educational Studies, Vol.5(1) August, pp.79-94. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 8, 2012); Revised (July 10, 2012); and Published (August 17, 2012).